Proposition of an agile knowledge-based process model. Issue 12 (2016) - Llamas, V.; Coudert, T.; Geneste, L.; Romero-Bejarano, J.C.; de Valroger, A.
Abstract: Modern organizations generally define and use standardized models of their processes. They manage their activities using such standards. In these processes, the generalization and reuse of knowledge is facilitated by the standardization. But it is sometimes difficult to react to unexpected events due to over-constrained standards. Companies need to become agile to survive to continuous changes in their environments. There is a requirement of agility for the processes in order to ensure constant responsiveness and flexibility. This necessity of agility can be achieved through a knowledge-based system. Therefore, this article proposes a knowledge-based agile process model in which agility is driven by the reuse of knowledge and experiences. For this purpose, agility operators are defined as formalized pieces of knowledge. A model of an agile process in which these operators are used is presented. The basis of a methodology describing incremental versions of the model is also presented. This "versioning" allows to formalize experiences and to capitalize them for future reuse. Finally, an application of the method to the problem solving domain is presented. It is shown how the standard 9 Steps process becomes more agile by deploying the proposed methodology.